A saúde no núcleo de Educação Infantil Paulistinha da Universidade Federal de São Paulo: uma análise documental - Paz, Adriana Oliveira [UNIFESP] (2016)
This research had as its main objective the analysis of health concepts and practices in the pedagogical project of the Early Childhood Education Center Paulistinha of the Universidade Federal de São Paulo (University of São Paulo) taking into account the official guidelines for education. The theoretical basis in which this research is based embraces the concepts of health, school children?s health and health education. Qualitative methods were used in this research and through the documental research nine official documents were analyzed, among those the Federal Education Guideline Law (Lei de Diretrizes e Bases da Educação Nacional), the Brazilian Federal Constitution, the Curricular Parameters and Guideline for Early Childhood Education (Parâmetros e Diretrizes Curriculares Nacionais para a Educação Infantil) and the Quality Indicator for Early Childhood Education. Two school documents were also analyzed: the school academic plan and the school statute. The data collected underwent a thematic content analysis. This research was approved by the Research Ethics Committee of the University of São Paulo. In the official documents were observed as a central theme the ?right to health?, from which the following dimensions were highlighted: promotion of health; global development; relation between care and education; safety and protection as health factors. In the documents from the Early Childhood Education Center Paulistinha it was possible to observe that besides the emphasis on the health context in which the Center is situated there is also the comprehension of the full development of children as a person as an institutional goal. As a result of this research a technical report that highlights improvements on school children?s health was produced in order to contribute in the production of the new pedagogical project of NEI-Paulistinha, process though which the school is in at the moment.